Study of Surah Ash-Shaffat Verse 102 and Surah Lukman Verses 16-19 (Al Azhar's Interpretation of Interpersonal Communication Between Parents and Children) - Wahyudin (Talenta Publisher, 2026)
This study aims to identify the patterns of interpersonal communication between parents and children contained in the Qur'an, specifically in Surah Ash-Shaffat verse 102 and Surah Luqman verses 16-19, and to analyze them through the perspective of Tafsir Al-Azhar by Buya Hamka. This research employs a qualitative method with a library research approach. Primary data was obtained from the Tafsir Al-Azhar book, while secondary data came from relevant books and journals. The findings indicate that both verses contain principles of effective interpersonal communication, namely: (1) Equality and Openness, as seen in the dialogue between Prophet Ibrahim and Ismail; (2) Empathy, reflected in Ismail's response; and (3) Positiveness, elaborated through Luqman's advice. This communication pattern is manifested in concrete behaviors such as appropriate diction, treating the child as a conversation partner, not turning one's face away, and not shouting. This research provides practical implications for parents in building harmonious communication with their children, which in turn can strengthen family resilience.